The solution to the system of equation are as follows:
1. x = 3, y = 0
2. x = -3 , y = 3
3. x= -9, y = -9
1.
y = x - 3
y = -2x + 6
multiply equation(i) by 2
2y = 2x - 6
y = -2x + 6
3y = 0
y = 0
x = 0 + 3
x = 3
2.
-x + 5y = 18
x + 4y = 9
9y = 27
y = 27 / 9
y = 3
x + 4(3) = 9
x = -3
3.
3x + 5y = -72
2x + 3y = -45
multiply equation(i) by 2 and equation(ii) by 3
6x + 10y = -144
6x + 9y = -135
y = -9
2x + 3(-9) = -45
2x = -45 + 27
2x = -18
x = -18 / 2
x = -9
learn more on linear combination here: https://brainly.com/question/11897796?referrer=searchResults